2010
DOI: 10.1016/j.ijid.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of HIV-infected patients hospitalized with bacterial community-acquired pneumonia

Abstract: The presence of HIV infection did not influence the clinical outcomes of CAP among patients assessed at CAPO centers. It is not intended that our results be extrapolated to populations receiving limited healthcare for advanced HIV disease, malnourishment and parasitic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 19 publications
2
34
1
1
Order By: Relevance
“…One area that has been particularly controversial, both in all cause CAP and specifically in pneumococcal pneumonia is whether the outcome is worse in HIV-infected versus HIV-uninfected persons [1]. While some studies have suggested that the outcome is no different [1,78,79], more recent studies in both allcause CAP and pneumococcal pneumonia have suggested that the mortality of CAP is higher in HIV-infected patients [1,35,69,82]. In one of these studies, which was in patients with bacteraemic pneumococcal pneumonia, when cases were stratified according to age and severity of illness, HIV infected patients had a higher mortality with a significant trend for increasing mortality in those with lower CD4 cell counts [35,69].…”
Section: Mortalitymentioning
confidence: 99%
“…One area that has been particularly controversial, both in all cause CAP and specifically in pneumococcal pneumonia is whether the outcome is worse in HIV-infected versus HIV-uninfected persons [1]. While some studies have suggested that the outcome is no different [1,78,79], more recent studies in both allcause CAP and pneumococcal pneumonia have suggested that the mortality of CAP is higher in HIV-infected patients [1,35,69,82]. In one of these studies, which was in patients with bacteraemic pneumococcal pneumonia, when cases were stratified according to age and severity of illness, HIV infected patients had a higher mortality with a significant trend for increasing mortality in those with lower CD4 cell counts [35,69].…”
Section: Mortalitymentioning
confidence: 99%
“…26 HIV-positive patients in this study had significantly lower severity scores than their seronegative counterparts, similar to what was observed in the CAPO international cohort study. 20,21 In our case, the difference can be explained by HIV-positive patients being younger, as age >65 years is a prognostic feature which contributes one point in the CURB-65 score, and there were no differences with respect to agecontrolled scores. This finding means other unaccounted factors guided clinicians in their decision to admit.…”
Section: Discussionmentioning
confidence: 54%
“…6,12,[14][15][16] Research has addressed this topic since the beginning of the HAART era, focusing on the course and outcome of CAP in HIV-positive patients. 5,13,15,[17][18][19] HIV infection is a known risk factor for bacteraemia, 5,19 but apparently not for higher mortality 5,18,20,21 or time to clinical stability. 20,21 Evidence on prediction of severity and resulting guidance on risk stratification and related management remains heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These risk factors include not being on ART, presence of pneumococcal antigen in urine for patients with pneumococcal pneumonia 169 and comorbid states such as liver cirrhosis (mostly from alcohol abuse) 170 . Compared with HIV sero negative patients and in situations where health care delivery may be described as optimal HIV infection appears not to increase the mortality risk in hospitalized patients with Community Acquired Pneumonia and neither does it lead to prolongation of hospital stay 171,172 . In patients with acute respiratory failure admitted to the ICU, the risk of death is related to extent of organ failure such as need for mechanical ventilation and use of vasopressor agents rather than HIV parameters such as CD4 T cell count, HIV plasma viral load or use of ART 173 .…”
Section: Outcomes Of Community Acquired Bacterial Pneumoniamentioning
confidence: 99%